Research progress in pediatric perioperative blood transfusion - LIAO Chenxi; LIAO Ren (Zhongguo shuxue zazhi)
Pediatric perioperative blood transfusion management requires individualized transfusion strategies and optimized management approaches due to children's physiological differences and higher risk of transfusion-related complications. This review discusses recent advancements in pediatric perioperative transfusion, focusing on unique characteristics, major complications, and preventive strategies, including restrictive and individualized transfusion approaches, antifibrinolytic medications, and optimal blood product selection and processing. Additionally, the paper highlights the potential role of big data, artificial intelligence, and multi-center clinical trials in advancing pediatric transfusion management and emphasizes the need for pediatric-specific transfusion guidelines and the development of blood substitutes. Moving forward, precise transfusion strategies and interdisciplinary collaboration will further enhance the safety and efficacy of pediatric perioperative transfusion, improving perioperative outcomes.